Digital Financial Literacy for Bamboo MSMEs: A SIAPIK Application Training Initiative in Lamongan - Wahidahwati; Rahayu, Rika; Zahro, Maratus; Maryam, Dewi; Kirana, Ardilla Ayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
East Java is a region rich in MSMEs in the food, beverage, craft, and other handmade goods sectors. One such area is Sukolilo Village, Lamongan, which is a renowned center for the bamboo craftsmen industry in Lamongan, participants were 10 bamboo craftsmen in Sukolilo Village. One of the reasons behind this initiative is the importance of financial literacy in the MSME sector, which is considered low and focuses only on profit/loss from a sales value. One thing that needs to be considered is the importance of determining the costs of the production process and determining the selling price, thus creating simple bookkeeping for MSMEs to increase financial literacy. One of the effective strategies in implementing community service activities in Sukolilo Village, Lamongan is to implement three stages of implementation, namely identification, training and mentoring, monitoring and evaluation. Based on the community service activities carried out in Sukolilo Village, which were attended by bamboo craftsmen in Sukolilo Village, Lamongan, it can be concluded that bamboo craftsmen in Sukolilo Village, Lamongan, started downloading the SIAPIK Bank Indonesia application from their respective cellphones via the Play Store and started using the SIAPIK application starting from registration, filling in business information, initial application settings, to entering financial data. The results of monitoring and evaluation indicate that bamboo craftsmen in Sukolilo Village require dedicated time and thought to prepare financial reports. Most bamboo craftsmen are housewives, so they require dedicated time to record their finances due to their busy daily schedules. This activity has clear outcomes is qualitative improvement. Implication this activity is to improve the quality of human resources, including in terms of expanding insight, knowledge, and improving skills.